PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN GIMKIT PADA MATERI NORMA DALAM ADAT ISTIADAT DAERAHKU - Salsabilla Dwi Aulia; Teti Rostikawati; Santa (STKIP Subang, 2025)
The purpose of this research is to be able to develop a learning evaluation product using gimkits on norm materials in the customs of my region, to be able to test the feasibility of the product. This research method uses the Research and Development (R&D) method with the ADDIE (analysis, design, development, implementation and evaluation) development model. This research involved 30 students, one media expert lecturer, one linguist, one material expert lecturer, and one material expert teacher. Based on the results of the validation carried out by the validator, the final results were obtained, namely, the results of the validation of media experts got 100%, the results of the validation of the lecturer material experts got 98%, and the results of the teacher validation got 100%, with an average result of 99.5%, it can be said that the product has the criteria of